OPTIMALISASI PENGGUNAAN MODA ANGKUTAN BUS TRANS LAMPUNG DALAM PENINGKATAN KONEKTIVITAS TRANSPORTASI WISATA KAWASAN TELUK LAMPUNG - Muhammad Zainal Ibad; Ayu Fitriyani; Rahayu Sulistyorini (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2021)
Pesawaran Regency is known to have advantages in the tourism sector. This can be seen from the number of tourists who continue to increase, especially on national holidays. The Provincial Government is collaborating with the Trans Lampung Bus by opening routes to tourist destinations, namely from Tanjung Karang Station - Ketapang Harbor. However, in practice, there is a tendency for tourists to use private transportation modes compared to public transportation modes that have been provided. Therefore, this study aims to find out how to increase tourist interest in using the Trans Lampung Bus public transportation route from Tanjung Karang Station to Ketapang Port as tourist transportation. There are three targets to achieve the research objectives, namely: 1. Knowing what factors influence the choice of mode; 2. Knowing the opportunities for using private and public transportation modes; 3. Make recommendations for optimizing public transportation mode. The analytical method used in this study is binary logistic regression and sensitivity. Based on the sensitivity analysis, it is known that the comfort factor has a higher sensitivity than the bus trip rit factor. Therefore, the comfort factor will be optimized first.